Human resource development competencies as predictors of agricultural extension agents' performance in Yemen - Obaid Khalil, Ali Hassan; Ismail, Maimunah; Suandi, Turiman; Silong, Abu Daud (Routledge, 2009)
Human resource development (HRD) issue is recognized as a significant factor for survival of organizations and professionals, including those in the sector of agricultural extension. Few empirical studies have examined the influence of HRD competency variables on agricultural extension agents' performance. The authors argue that HRD competency variables such as leadership development, communication, programme planning, programme implementation and programme evaluation could predict agricultural extension agents' performance. Questionnaire data were collected from a sample of 290 extension agents in Yemen to discover if HRD competencies affect the performance of extension agents. Regression analysis shows that three variables - competencies in programme implementation, programme evaluation and programme planning - contributed significantly to the performance of extension agents. These predictors explain 42.2% of the variance in the job performance model.